Assessing stress, anxiety, and depression in children and adolescents: Validation of the DASS-Y in Poland - Andrzej Śliwerski; Karolina Koszałkowska; Izabela Socha (PLoS ONE, 2025)
Background The Depression Anxiety Stress Scales (DASS-21) is a widely used measure of negative emotional states in adults and adolescents. A youth version (DASS-Y) was recently developed and validated to address the developmental needs of younger populations. While the DASS-Y has shown promising psychometric properties in several languages, no Polish adaptation has been conducted to date. This study aimed to validate the Polish version of the DASS-Y and assess its psychometric performance in a sample of children and adolescents. Methods A total of 344 children and adolescents aged 9–17 years were recruited using a school-based convenience sampling strategy between January 6 and February 16, 2025. Participants completed a sociodemographic questionnaire, the Polish version of the DASS-Y, the Children’s Depression Inventory (CDI), and the Self-Assessment Manikin (SAM) scale. Results CFA supported the original three-factor structure of the DASS-Y with satisfactory model fit indices. The subscales demonstrated excellent internal consistency, with Cronbach’s alpha and McDonald’s omega values exceeding 0.85. The DASS-Y subscales correlated significantly with the CDI and SAM scales in expected directions, supporting convergent and discriminant validity. Metric invariance across genders was established, though scalar invariance was not fully supported, indicating potential differences in item intercepts between boys and girls. Conclusions The Polish version of the DASS-Y is a reliable and valid tool for assessing depression, anxiety, and stress in Polish children and adolescents. While the instrument functions similarly across genders in terms of structure, caution is advised when comparing mean scores between boys and girls due to partial scalar invariance. Future research should explore the DASS-Y’s applicability in clinical settings and its sensitivity to changes over time.